Genomic heterogeneity and copy number variant burden are associated with poor recurrence‐free survival and 11q loss in human papillomavirus‐positive squamous cell carcinoma of the oropharynx. Issue 15 (5th April 2021) - Schrank, Travis P.; Lenze, Nicholas; Landess, Lee P.; Hoyle, Alan; Parker, Joel; Lal, Asim; Sheth, Siddharth; Chera, Bhishamjit S.; Patel, Samip N.; Hackman, Trevor G.; Major, M. Ben; Issaeva, Natalia; et al.
Abstract : Background: Human papillomavirus–positive (HPV+) squamous cell carcinoma of the oropharynx (OPSCC) is the most prevalent HPV‐associated malignancy in the United States. Favorable treatment outcomes have led to increased interest in treatment de‐escalation to reduce treatment morbidity as well as the development of prognostic markers to identify appropriately low‐risk patients. Intratumoral genomic heterogeneity and copy number alteration burden have been demonstrated to be predictive of poor outcomes in many other cancers; therefore, we sought to determine whether intratumor heterogeneity and genomic instability are associated with poor outcomes in HPV+ OPSCC. Methods: Tumor heterogeneity estimates were made based on targeted exome sequencing of 45 patients with HPV+ OPSCC tumors. Analysis of an additional cohort of HPV+ OPSCC tumors lacking matched normal sequencing allowed copy number analysis of 99 patient tumors. Results: High intratumorally genomic heterogeneity and high numbers of copy number alterations were strongly associated with worse recurrence‐free survival. Tumors with higher heterogeneity and frequent copy number alterations were associated with loss of distal 11q, which encodes key genes related to double‐strand break repair, including ATM and MRE11A. Conclusions: Both intratumor genomic heterogeneity and high‐burden copy number alterations are strongly associated with poor recurrence‐free survival in patients with HPV+ OPSCC. The drivers of genomic instability and heterogeneity in these tumors remains to be elucidated. However, 11q loss and defective DNA double‐strand break repair have been associated with genomic instability in other solid tumors. Copy number alteration burden and intratumoral heterogeneity represent promising avenues for risk stratification of patients with HPV+OPSCC. Abstract : Molecular markers are needed to determine which human papillomavirus (HPV)‐positive patients with squamous cell carcinoma of the oropharynx (OPSCC) are best served by reduced intensity treatment, which has the potential to reduce severe treatment‐related morbidity. We demonstrate that 11q‐related copy number variant burden and heterogeneity are highly associated with poor recurrence‐free survival in patients with HPV‐positive OPSCC and may have potential as translational biomarkers.